2020
DOI: 10.1101/2020.02.26.965715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of colonization history on the composition of ecological systems

Abstract: Observational studies of ecological systems have shown that different species compositions can arise from distinct species arrival orders during community assembly-also known as colonization history. However, it is still unclear under which conditions colonization history will dominate community composition. Yet, this is important in order to understand and anticipate the impact of species arrivals on the biodiversity that we observe in both nature and experiments. To address this fundamental question, here we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
6
2
Order By: Relevance
“…Second, we have shown that the probability of observing contingent exclusion decreases with community size (Figure 4). This result is contrary to the naive expectation that contingent exclusion dominates in larger communities, derived from randomly constructed communities (Zhao et al ., 2020). However, it has remained unclear what happens when communities are structured following a strong deterministic component of population dynamics (Fukami, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Second, we have shown that the probability of observing contingent exclusion decreases with community size (Figure 4). This result is contrary to the naive expectation that contingent exclusion dominates in larger communities, derived from randomly constructed communities (Zhao et al ., 2020). However, it has remained unclear what happens when communities are structured following a strong deterministic component of population dynamics (Fukami, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…2003; Fukami & Nakajima 2011; Fukami 2015; Zhao et al . 2020). While a progressive, deterministic view of assembly would call for a mathematisation of the problem, the more nuanced view that emerged led to an impasse in the development of a theory of assembly – as put by Drake et al .…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, the study of assembly has unveiled a complicated picture (Drake 1991;Law & Morton 1993;Warren et al 2003;Schreiber & Rittenhouse 2004)in general, assembly is anything but predictable: small changes to the order, size and timing of invasions can result in completely different local communities (Drake 1991), giving rise to priority effects and alternative histories (Warren et al 2003;Fukami & Nakajima 2011;Fukami 2015;Zhao et al 2020). While a progressive, deterministic view of assembly would call for a mathematisation of the problem, the more nuanced view that emerged led to an impasse in the development of a theory of assemblyas put by Drake et al (2012) 'analytical solutions simply do not exist for systems of containing many species [...] In fact, the dynamics seen in many species systems suggest little to no role for a purely analytical approach'.…”
Section: Introductionmentioning
confidence: 99%
“…In the intervening decades, the study of assembly has unveiled a much more complicated picture (Drake, 1991;Law & Morton, 1993;Schreiber & Rittenhouse, 2004;Warren et al, 2003)-in general, assembly is anything but predictable: small changes to the order, size, and timing of invasions can result in completely different local communities (Drake, 1991). The dependency of the final community on the order of arrival of invaders gives rise to "historical contingencies" driven by priority effects (Fukami, 2015), and much effort went into determining whether and when these alternative histories can emerge (Fukami & Nakajima, 2011;Warren et al, 2003;Zhao et al, 2020). Similarly, the density at which the invader enters the community can influence the outcome, a complication compounded by the fact that the local community could be coexisting at a limit-cycle or chaotic attractor-and as such the invader could establish at certain times, but not others.…”
Section: Introductionmentioning
confidence: 99%